Frequency of EGFR Mutation in Nsclc and Its Relationship with Clinicopathological Features: A Multicenter Asmo Trial - Yuksel, Sinemis; Kodaz, Hilmi; Yildiz, Ibrahim; Odabasi, Hatice; Ocak, Ayse; Bayoglu, Ibrahim V.; Gumus, Mahmut (Elsevier Science Inc, 2015)
[Abstract Not Available]
Keywords: EGFR mutation; non small cell lung cancer; molecular testing; survival